In-situ analysis energy level alignment at solution processed HAT(CN)6/PVK (PVK:TAPC) interface via XPS and UPS - Talik N.A.; Yap B.K.; Tan C.Y.; Whitcher T.J. (Elsevier B.V., 2023)
Heterojunctions; Interfaces (materials); Light emitting diodes; Organic light emitting diodes (OLED); Photoelectrons; Photons; Charge-generation layers; Electron extraction; Energy differences; Energy level alignment; Poly(9-vinylcarbazole); Solution-processed; Tandem OLED; Vacuum level shift; X ray photoelectron spectroscopy